Immunology of the Lymphatic System - Santambrogio, Laura.; Santambrogio, Laura. (Springer New York : Imprint: Springer, 2013)
Immunology of the Lymphatic System is a comprehensive study of the lymphatic system and its immunological role. It begins with lymphatic capillaries, their origin and development. It addresses lymph circulation, in general, with a special emphasis on lymph circulation in parenchymal organs. The next section focuses on lymph nodes, subcortical circulation and the conduit system. It discusses organs with no lymphatic system, such as the brain. Finally, it covers lymph composition and cells in the lymph. While primarily basic research, the volume touches upon elements of the clinical, as well, broadening its scope and appeal.